Slang and Informal Language in the Disney Film “Encanto”: A Sociolinguistic Analysis - Almunawarah, Nadia; Moetia, Meristiaka (Pencerah, 2025)
This study examines the presence and types of slang in the animated film Encanto, with the aim of identifying the categories of slang expressions and determining the most frequently used type. While previous research has often focused on slang in youth subcultures, music, or everyday interaction, less attention has been given to how slang is embedded in family-oriented animated films that reach global audiences. Using a descriptive qualitative method, the data were gathered through repeated viewings of the film and analyzed with Allan and Burridge’s (2006) framework, which classifies slang into five types: fresh and creative, flippant, imaginative rhyming, acronymic, and clipping. The analysis revealed 125 slang expressions, distributed as follows: 8% fresh and creative slang, 6% clipping slang, 27% imaginative rhyming slang, and 59% flippant slang, with flippant slang emerging as the most dominant. These findings highlight how Encanto relies on informal, humorous, and playful language to engage younger audiences. Beyond entertainment, this study contributes to sociolinguistic discussions of language variation in media and provides insights for educators into how popular films mirror and influence children’s exposure to informal language.